Cell-laden injectable microgels: Current status and future prospects for cartilage regeneration. (December 2021) - Nguyen, Thuy P.T.; Li, Fanyi; Shrestha, Surakshya; Tuan, Rocky S.; Thissen, Helmut; Forsythe, John S.; Frith, Jessica E.
Abstract: Injectable hydrogels have been employed extensively as versatile materials for cartilage regeneration due to their excellent biocompatibility, tunable structure, and ability to accommodate bioactive factors, as well as their ability to be locally delivered via minimally invasive injection to fill irregular defects. More recently, in vitro and in vivo studies have revealed that processing these materials to produce cell-laden microgels can enhance cell-cell and cell-matrix interactions and boost nutrient and metabolite exchange. Moreover, these studies have demonstrated gene expression profiles and matrix regeneration that are superior compared to conventional injectable bulk hydrogels. As cell-laden microgels and their application in cartilage repair are moving closer to clinical translation, this review aims to present an overview of the recent developments in this field. Here we focus on the currently used biomaterials and crosslinking strategies, the innovative fabrication techniques being used for the production of microgels, the cell sources used, the signals used for induction of chondrogenic differentiation and the resultant biological responses, and the ability to create three-dimensional, functional cartilage tissues. In addition, this review also covers the current clinical approaches for repairing cartilage as well as specific challenges faced when attempting the regeneration of damaged cartilage tissue. New findings related to the macroporous nature of the structures formed by the assembled microgel building blocks and the novel use of microgels in 3D printing for cartilage tissue engineering are also highlighted. Finally, we outline the challenges and future opportunities for employing cell-laden microgels in clinical applications.